Romanian Translation and Cultural Adaptation of the Seizure Severity Questionnaire - Ionut-Horia Cioriceanu; Dan-Alexandru Constantin; Bianca Zamfirescu; Petru Cezar Podasca; Luigi Geo Marceanu; Liliana Rogozea (MDPI AG, 2024)
The aim of this study was to report the translation into Romanian of the Seizure Severity Questionnaire (SSQ), an instrument for the evaluation of the frequency and severity of epileptic seizures, and the results of applying it to a group of patients with epilepsy evaluated at a hospital in Romania. Methods: Four translators were involved in obtaining conceptual analogies and the cultural importance of the translated notions. The final version was obtained for the Romanian population, with the same appearance as the original instrument. Sixty-seven patients with epilepsy completed the SSQ and the Patient-Weighted Quality of Life in Epilepsy Inventory-QOLIE-31-P. Results: Females had a lower mean SSQ total score (TS) and perceived seizures less seriously than men. Patients with epilepsy with aura had a higher mean SSQ TS, with a more severe seizure perception, compared to those without aura. According to the frequency of seizures, patients with epilepsy with rare seizures had the lowest mean SSQ total score (TS) compared to those with frequent seizures. Patients who were on monotherapy had a less severe perception of epileptic seizures compared to those who were treated with two or more antiepileptic drugs. All QOLIE-31-P domains and TS correlated statistically significantly with the SSQ TS. Conclusions: This study explored SSQ translation, evaluated preliminary results, and showed the correlation between seizure frequency and severity, clinical factors, and quality of life. This tool could be useful for measuring seizure severity in Romanian patients with epilepsy and conducting comparative studies.